2019
DOI: 10.1371/journal.pntd.0006987
|View full text |Cite
|
Sign up to set email alerts
|

Antibody responses to Plasmodium vivax Duffy binding and Erythrocyte binding proteins predict risk of infection and are associated with protection from clinical Malaria

Abstract: Background The Plasmodium vivax Duffy Binding Protein (PvDBP) is a key target of naturally acquired immunity. However, region II of PvDBP, which contains the receptor-binding site, is highly polymorphic. The natural acquisition of antibodies to different variants of PvDBP region II (PvDBPII), including the AH, O, P and Sal1 alleles, the central region III-V (PvDBPIII-V), and P . vivax Erythrocyte Binding Protein regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 45 publications
10
30
1
Order By: Relevance
“…Similarly, an earlier study demonstrated that an IgG1 response against PvEBP domain (161-641 aa.) was dominant in an age-dependent manner in vivax patients [40]. Our study confirmed that only the IgG response against PvEBP-RIII-V (480-676 aa.)…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similarly, an earlier study demonstrated that an IgG1 response against PvEBP domain (161-641 aa.) was dominant in an age-dependent manner in vivax patients [40]. Our study confirmed that only the IgG response against PvEBP-RIII-V (480-676 aa.)…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, antibodies against PvEBP-RII were useful for serological marker of recent malaria exposure, with a half-life estimated at 734 days [42]. Anti-PvEBP-RII antibodies were predominant IgG1 and IgG3 which is similar to other PfEBAs-RII to mediate opsonic phagocytosis [39,40]. However, PvEBP-RII showed highest genetic polymorphism within pvebp-ecto domains.…”
Section: Discussionmentioning
confidence: 97%
“…shown that IgG subclass profiles to P. falciparum [45] and P. vivax [46][47][48] differed among malaria antigens and that the subclass predominance is influenced by age and increasing exposure to infection. High IgG1 and IgG3 levels have been associated with long-term exposure to P. vivax [40,48].…”
Section: Discussionmentioning
confidence: 99%
“…Functional analyses indicated that region II of this gene bound to both Duffy-positive and Duffy-negative reticulocytes, although at a lower frequency compared to PvDBP, suggestive of its role in erythrocyte invasion [40]. Both PvEBP1 and PvEBP2 genes exhibit high genetic diversity and are common antibody binding targets associated with clinical protection [41,42]. Other proteins such as tryptophan-rich antigen gene (TRAg), anchored micronemal antigen (GAMA), and Rhoptry neck protein (RON) have also been suggested to play a role in red cell invasion, especially in low-density infections [43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%